2004
DOI: 10.1016/j.marmicro.2004.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Population ecology and shell chemistry of a phytal ostracode species (Loxoconcha matagordensis) in the Chesapeake Bay watershed

Abstract: Population ecology and shell chemistry were studied in the phytal ostracode Loxoconcha matagordensis (Swain 1955) collected from Zostera marina seagrass beds in the Chesapeake Bay to provide seasonal constraints on shell secretion time for paleothermometry. Population density and age structure were defined by two main breeding cycles that occurred between 01 to 15 June and 02 to 16 August 2001. The time interval between breeding cycles was~2 months and total juvenile standing crop increased almost three-fold b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…A total of 258 samples from MD03-2661 yielded L. matagordensis suitable for analysis (see chronology); the RD-2209 record included 450 analyses . Mg/Ca ratios were converted to warm-season temperature using the calibration equation y =0.644x −2.4284 (r 2 =0.805) derived from field, culturing and laboratory analyses of Loxoconcha from Chesapeake Bay and the adjacent continental shelf (Dwyer et al, 2002;Cronin et al, 2003;Vann et al, 2004). These calibration studies demonstrated that temperature is the primary factor influencing Chesapeake Bay Loxoconcha Mg/Ca ratios and, at least over the sampled salinity range (~15-35 psu), salinity does not appear to be important.…”
Section: Proxy Methodsmentioning
confidence: 99%
“…A total of 258 samples from MD03-2661 yielded L. matagordensis suitable for analysis (see chronology); the RD-2209 record included 450 analyses . Mg/Ca ratios were converted to warm-season temperature using the calibration equation y =0.644x −2.4284 (r 2 =0.805) derived from field, culturing and laboratory analyses of Loxoconcha from Chesapeake Bay and the adjacent continental shelf (Dwyer et al, 2002;Cronin et al, 2003;Vann et al, 2004). These calibration studies demonstrated that temperature is the primary factor influencing Chesapeake Bay Loxoconcha Mg/Ca ratios and, at least over the sampled salinity range (~15-35 psu), salinity does not appear to be important.…”
Section: Proxy Methodsmentioning
confidence: 99%
“…It is also important to consider the seasonal ecology and time of shell secretion in both Loxoconcha and Elphidium for interpreting paired δ 18 O foram and Mg/Ca values. Ostracodes grow in 8 or 9 discrete molt stages and studies of the seasonal ecology of Loxoconcha matagordensis [ Vann et al , 2004; Cronin et al , 2005] indicate that most adults secrete their shells during spring and summer seasons and thus the paleotemperature record is mainly a warm season record. Other temperate species of Loxoconcha have similar seasonal ecology and grow adult shells during spring and/or summer.…”
Section: Calibration and Verificationmentioning
confidence: 99%
“…To reconstruct the CB SL variability over the past 2000 years, we applied the 1.94 and 1.48 cm sensitivity values to paleo‐SST records generated from magnesium/calcium (Mg/Ca) paleothermometry [ Cronin et al , , ; Vann et al , ]. Mg/Ca in calcite (CaCO 3 ) shells of the ostracode Loxoconcha (crustacea) is controlled by the water temperature at which the adult animal grows its shell during molting.…”
Section: Methodsmentioning
confidence: 99%